2018
DOI: 10.24130/eccd-jecs.196720182279
|View full text |Cite
|
Sign up to set email alerts
|

Okul öncesi kaynaştırma sınıfında öğretmen

Abstract: Öz: Kaynaştırma programlarının temel amacı, özel gereksinimli çocukların içinde yaşadığı topluma uyum becerileri kazandırmaktır; aynı zamanda bu uygulamaların toplumda farklılıklara saygı ve özel gereksinimli bireylerin sosyal kabulünde artış sağlayacağı da düşünülmektedir. Kaynaştırma programlarının amacına ulaşmasında en etkili kişi olan öğretmenler bu uygulamalarda genel olarak üç önemli sorunla karşılaşmaktadır: Özel gereksinimli çocukla nasıl iletişim kurabilirim; problemlerle nasıl baş edebilirim? Eğitim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 2 publications
1
1
0
4
Order By: Relevance
“…This finding is in parallel with the existing studies in the literature (Acarlar et al, 2003;Batmaz & Çermik, 2019;Cooc;2019;Familia-Garcia, 2001;Kamalı-Arslantaş & Kocaöz, 2023;Kamalı Arslantaş & Yalçın, 2023;Kocaoğlu et al, 2023;Taş, 2021;Zanazzi, 2018;Westwood & Graham, 2003;Woodcock & Woolfson, 2019). When the literature is examined, it is emphasized that teachers' level of knowledge about individuals with SEN and inclusive education is an important factor in creating effective learning environments (Metin, 2018). Heiman (2014) found that teachers' insufficient knowledge of inclusive education increases their anxiety levels towards the teaching process.…”
Section: Discussionsupporting
confidence: 75%
“…This finding is in parallel with the existing studies in the literature (Acarlar et al, 2003;Batmaz & Çermik, 2019;Cooc;2019;Familia-Garcia, 2001;Kamalı-Arslantaş & Kocaöz, 2023;Kamalı Arslantaş & Yalçın, 2023;Kocaoğlu et al, 2023;Taş, 2021;Zanazzi, 2018;Westwood & Graham, 2003;Woodcock & Woolfson, 2019). When the literature is examined, it is emphasized that teachers' level of knowledge about individuals with SEN and inclusive education is an important factor in creating effective learning environments (Metin, 2018). Heiman (2014) found that teachers' insufficient knowledge of inclusive education increases their anxiety levels towards the teaching process.…”
Section: Discussionsupporting
confidence: 75%
“…In order to make cooperation mechanisms effective in inclusive education interventions, results have been obtained for cooperation between school, family, teacher; cooperation between parents of students with and without disabilities; cooperation between teacher and school administration; cooperation between school and counseling and research center. For effective inclusive education intervention, a multi-dimensional interaction and collaboration process should be established between the parties (Taylor, Smiley & Richards, 2009;McMillan, 2008;Lee & Low, 2013;Metin, 2018). In research on inclusive education, the lack of cooperation among the parties has been identified as an important problem in inclusive education interventions (Çankaya & Korkmaz, 2012;Fuchs, 2010;Hemmingsson, Gustavsson & Townsend, 2007;Hui, 2015).…”
Section: Discussion Regarding the Third Sub-problemmentioning
confidence: 99%
“…Bu sürecin omurgasını oluşturan öğretmenlerin de olumlu tutumlara, gerekli bilgi ve becerilere sahip olması hem ÖG hem de NGG öğrencilerin gelişimi için çok önemlidir (Bayar & Üstün, 2017;Forlin, Earle, Loreman, & Sharma, 2011). Öğretmenlerin kaynaştırma sürecinde gereksinim duydukları yeterliliklere bakıldığında ise planlama süreçleri, özel eğitim yöntem ve tekniklerine hâkimiyet, sınıf yönetimi, davranış problemleri ile başa çıkabilmek, uyarlama ve iş birliği gibi pek çok niteliğe ihtiyaç duydukları görülmektedir (Akiba, Le Tendre & Scribner, 2007;Elmacı & Karaaslan, 2021;Erdem & Yıldız, 2017;Hssien, Brown, & Bortoli, 2009;Metin, 2018). Bu niteliklerin hizmet öncesi eğitimlerde edinilmesi her zaman mümkün olmamaktadır.…”
Section: Introductionunclassified